2016
DOI: 10.1039/c5fo01270h
|View full text |Cite
|
Sign up to set email alerts
|

Pro198Leu polymorphism affects the selenium status and GPx activity in response to Brazil nut intake

Abstract: Selenoproteins play important roles in antioxidant mechanisms, and are thus hypothesised to have some involvement in the pathology of certain types of dementia. Mild cognitive impairment (MCI) and Alzheimer's disease (AD) are both thought to involve impaired biological activity of certain selenoproteins. Previously, supplementation with a selenium-rich Brazil nut (Bertholletia excelsa) has shown potential in reducing cognitive decline in MCI patients, and could prove to be a safe and effective nutritional appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 59 publications
2
41
1
2
Order By: Relevance
“…Furthermore, it was found that changes in plasma triglycerides in response to omega-3 fatty acid supplementation could be modulated by the effect of polymorphisms and DNA methylation on expression levels of key genes identified by genome-wide association studies [104]. Additionally, genetic variants in genes encoding the selenoproteins glutathione peroxidase ( GPX1 ) and selenoprotein P ( SEPP ) could influence their gene expressions in response to supplementation with a selenium-rich Brazil nut, suggesting a possible role in the nutritional treatment of chronic degenerative conditions [105]. …”
Section: Diet and Epigenetic Signaturesmentioning
confidence: 99%
“…Furthermore, it was found that changes in plasma triglycerides in response to omega-3 fatty acid supplementation could be modulated by the effect of polymorphisms and DNA methylation on expression levels of key genes identified by genome-wide association studies [104]. Additionally, genetic variants in genes encoding the selenoproteins glutathione peroxidase ( GPX1 ) and selenoprotein P ( SEPP ) could influence their gene expressions in response to supplementation with a selenium-rich Brazil nut, suggesting a possible role in the nutritional treatment of chronic degenerative conditions [105]. …”
Section: Diet and Epigenetic Signaturesmentioning
confidence: 99%
“…No difference was observed in T-carriers. This genetic variation was associated with increased GPX1 mRNA expression in other Brazilian work conducted with Alzheimer's patients, but the authors found the increase in T-carriers instead of CC (CARDOSO et al, 2015a). Although some studies have investigated the association of this variation with differences on GPx1 activity JABLONSKA et al, 2009), few studies have associated this variation with GPX1 gene expression.…”
Section: Discussionmentioning
confidence: 72%
“…Alzheimer's patients also found an increase in GPX1 mRNA expression after supplementation with 1 unit of Brazil nut for 6 months (CARDOSO et al, 2015a). A possible explanation for this variation in response to Se supplementation is the presence of genetic variants, which most of the aforementioned works have not considered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations